Preparation and Evaluation of Starch Hydrogel/Contact Lens Composites as Epigallocatechin Gallate Delivery Systems for Inhibition of Bacterial Adhesion - Lianghui Zhao (Frontiers Media S.A., 2021)
Microbial infections caused by wearing contact lenses has become a major health problem, so the design and development of antibacterial contact lenses has attracted widespread attention. To safely and effectively inhibit bacterial adhesion of contact lenses, we have facilely prepared epigallocatechin gallate (EGCG) loaded starch hydrogel/contact lens composites by in-situ free radical polymerization of the mixture containing 2-hydroxylethyl methacrylate, methacrylic acid and ethylene glycol dimethacrylate. The adequate transmittance of the resulting contact lenses was characterized by ultraviolet-visible spectrophotometry, and their satisfactory stability was examined using differential scanning calorimetry and thermogravimetric analysis. Whereafter, cytotoxicity and degradation experiments were performed to investigate the biocompatibility and degradability of the contact lenses. The results showed the nontoxicity and good degradability of the composites. Besides, the capacity of the contact lenses for in vitro release of EGCG was also evaluated, and the results showed that the EGCG in these contact lenses can be sustainably released for at least 14 days. Further bacterial adhesion assay suggested that the EGCG loaded starch hydrogel/contact lenses could significantly reduce the adhesion of Pseudomonas aeruginosa compared to the control. The EGCG loaded starch hydrogel/contact lens composites provide a potential intervention strategy for preventing ocular microbial infections and inhibiting bacterial keratitis.